Hippocampal deformation mapping in MRI negative PET positive temporal lobe epilepsy. Issue 6 (10th October 2007) - Hogan, R E; Carne, R P; Kilpatrick, C J; Cook, M J; Patel, A; King, L; O'Brien, T J
Abstract : Objectives: To compare hippocampal surface structure, using large deformation high dimensional mapping (HDM-LD), in subjects with temporal lobe epilepsy (TLE) with (HS+ve) and without (HS−ve) hippocampal sclerosis. Methods: The study included 30 HS−ve subjects matched with 30 HS+ve subjects from the previously reported epilepsy patient cohort. To control for normal right–left asymmetries of hippocampal surface structure, subjects were regrouped based on laterality of onset of epileptic seizures and presence of HS. Gender ratio, age, duration of epilepsy and seizure frequency were calculated for each of the four groups. Final HDM-LD surface maps of the right and left TLE groups were compared to define differences in subregional hippocampal involvement within the groups. Results: There were no significant differences in comparisons of the left TLE (left HS−ve compared with HS+ve) or right TLE (right HS−ve compared with HS+ve) groups with respect to age, duration of epilepsy or seizure severity scores. HDM-LD maps showed accentuated surface changes over the lateral hippocampal surface, in the region of the Sommer sector, in the hippocampi affected by HS. However, HS−ve hippocampi showed maximal surface changes in a different pattern, and did not involve the region of Sommer sector. Conclusion: We conclude that differences in segmental volume loss between the HS−ve and HS+ve groups are suggestive that the underlying pathophysiology of hippocampal changes in the two groups is different, and not related to chronic seizure duration or severity.